Eisosomes and membrane compartments in the ascomycetes: A view from Aspergillus nidulans - Scazzocchio, Claudio (Landes Bioscience, 2011)
Eisosomes are punctate structures located in the cytoplasmic side of the cell membrane of ascomycetes. In Saccharomyces cerevisiae they coincide topologically with and are necessary for the organisation of specific membrane domains. The eisosomal proteins are universally and quite strictly conserved in the sub-phylum, however this evolutionary conservation is in apparent contradiction with an elusive functional significance. The comparative analysis of the eisosomes of S. cerevisiae and Aspergillus nidulans reveal striking differences in the assembly and developmental fate of these structures between these two model organisms.